(untitled) (Vietnam Journal of Community Medicine, 2022)
Backgroud: Disorders of sex development (DSDs) are a group of diseases caused by many different causes, including DSDs due to anormal stage of sex organ differentiation and hormon synthesis disorders. Objectives: All patients diagnosed DSDs at Vietduc university hospital from 2015 to 2022. Materials and method: Cross-sectional descriptive study. Results: 53 patients with DSDs include 25 patients with 5α-reductase type 2 deficiency, 15 patients with congenital adrenal hyperplasia, 3 patients with androgen insensitivity syndrome, 5 patient with complete gonadal dysgenesis, 1 patient with MRKH syndrome, 4 patients with Ovotesticular. Conclusions: At Vietduc university hospital, we are diagnosed some causes DSDs. In woman, DSDs most common were congenital adrenal hyperplasia, Mayer Rokitansky Kuster Hauser syndrome was rare in 46,XX patient. Enzyme 5α-reductase type 2 deficiency, androgen insensitivity syndrome cause DSDs in man with pure 46,XY. Ovotesticular and complete gonadal dysgenesis cause many cases DSDs both men and women.